Early Ulysses Documents: Uncovering Joyce Re-covering His “Oxen’s” End - P. Sullivan, James (FOCUS: Papers in English Literary and Cultural Studies, 2002)
For some time, Joyce studies have dealt with questions of text generation, how from one stage to another, the shape of his work emerged. With Ulysses, the focus has been, with few exceptions, on later versions, primarily those between the fair copy and the first edition of 1922. Earlier phases ofthe novel have been cast in the latter’s shadow, as ifjudged too fragmented, too elusive, and too little related to its final configuration to deserve serious consideration. Ofwhat relevance could the rejected content of quick sketches or other false starts prove?